KEGIATAN BERMAIN BOLA UNTUK MENINGKATKAN PENGENALAN ARAH GERAK SISWA TUNAGRAHITA SEDANG - Hardiyanti, Siti (Jurnal Pendidikan Khusus, 2016)
ABSTRACTMentally disabled child is one of the children with special needs that have independence that should be increased. It is because the mentally disabled child has a limit in doing social activity and has the level of IQ under the average of the normal child. So, the child still needs help from the other people to do some activities. Understanding the instructions that dealing with directions is one of the examples. Mentally disabled children have trouble in identifying the movement directions especially the movements to the right, left, forward and backward direction. In this case, the activity play ball is used to increase the level of direction recognizing for the mid-level-mentally-disabled students. The purpose of this study is to increase the skill of direction recognizing to the mid-level-mentally-disabled students in the 3rd Grade SDLB Muhammadiyah Jombang. This research is quantitative researches with pre-experiment design which using pre-test post-test design, with six subjects which are mid-level-mentally-disabled children. The data analysis is using non-parametric statistic with wilcoxon test.The research shows that there is an increase of direction recognizing level of the students in 3rd grade of SDLB Muhammadiyah Jombang by activity play ball, fit into the result of the pre-test marks average which is 44.41 and the average of the post-test which is 63.01. From the result of the data analysis, it can be concluded that the calculation number is from Z = 2.20. That number than compared with the critical value 5% Ztable which is 1.96. This fact proves that the value of Zcount > 1.96 which means Ha is received and Ho is rejected. This means that football game is effective in escalating the skill of direction recognition by the mid-level-mentally-disabled students in 3rd grade of SDLB Muhammadiyah Jombang.Keywords: Movement direction, activity play ball